Pengembangan Video Pembelajaran Berbasis Kontekstual Materi SPLDV untuk Meningkatkan Kemampuan Literasi Matematis Peserta Didik - Husnah, Asmaul; Nur, Fitriani; Sriyanti, A.; Sulasteri, Sri; Mattoliang, Lisnasari Andi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
Technology in learning must be optimized, one of which is using learning. This study aims to determine the process of developing learning videos and the validity, practicality, and effectiveness of learning videos. This type of research is Research and Development research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used are a validation sheet, a learning implementation observation sheet, a student activity observation sheet, a teacher response questionnaire, a student response questionnaire, and a mathematical literacy ability test. The research subjects were students of class VIII, 2 MTs Negeri Gowa. The results showed that the validation analysis achievement by the validator team was 3.83, which is a very valid category. Practicality criteria of 90.38% with a very positive response, and the results of observations of learning implementation 1.85, with the category fully implemented. The results of the effectiveness criteria were 85.43% with a positive response, 71.05% student activity observation analysis with a good category, and 76.05%. So it is concluded that the context-based learning video on SPLDV material to improve students' mathematical literacy skills is of good quality, as evidenced by the average student being at level 4, namely 68.42%. So that it is effectively applied in the learning process because it meets the criteria of validity, practicality, and effectiveness. Other researchers can also develop videos with different tools and materials.